Galectin-3 (MAC-2) Controls Microglia Phenotype Whether Amoeboid and Phagocytic or Branched and Non-phagocytic by Regulating the Cytoskeleton - Reichert, Fanny; Rotshenker, Shlomo (Frontiers in Cellular Neuroscience, 2019)
Myelin surrounding central nervous system (CNS) axons breaks down in multiple sclerosis (MS) and following traumatic axonal injury. Myelin-debris so produced is harmful to repair since it impedes remyelination in MS and the regeneration of traumatized axons. These devastating outcomes are largely due to inefficient removal by phagocytosis of myelin-debris by microglia. Therefore, revealing mechanisms that control phagocytosis is vital. We previously showed that in phagocytosis, filopodia and lamellipodia extend/engulf and then retract/internalize myelin-debris. Moreover, cofilin activates phagocytosis by advancing the remodeling of actin filaments (i.e., existing filaments disassemble and new filaments assemble in a new configuration), causing filopodia/lamellipodia to protrude, and furthermore, Galectin-3 (formally named MAC-2) activates phagocytosis by enhancing K-Ras.GTP/PI3K signaling that leads to actin/myosin-based contraction, causing filopodia/lamellipodia to retract. To understand further how Galectin-3 controls phagocytosis we knocked-down (KD) Galectin-3 expression in cultured primary microglia using Galectin-3 small-hairpin RNA (Gal-3-shRNA). KD Galectin-3 protein levels reduced phagocytosis extensively. Further, inhibiting nucleolin (NCL) and nucleophosmin (NPM), which advance K-Ras signaling as does Galectin-3, also reduced phagocytosis. Strikingly and unexpectedly, knocking down Galectin-3 resulted in a dramatic transformation of microglia morphology from “amoeboid-like” to “branched-like,” rearrangement of actin filaments and inactivation of cofilin. Thus, Galectin-3 may control microglia morphology and phagocytosis by regulating the activation state of cofilin, which, in turn, affects how actin filaments organize and how stable they are. Furthermore, our current and previous findings together suggest that Galectin-3 activates phagocytosis by targeting the cytoskeleton twice: first, by advancing cofilin activation, causing filopodia/lamellipodia to extend/engulf myelin-debris. Second, by advancing actin/myosin-based contraction through K-Ras.GTP/PI3K signaling, causing filopodia/lamellipodia to retract/internalize myelin-debris.